(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
Foreign writers flocked to write the history of Algeria during the Ottoman era, after the latter was at the height of its power and international elevation, and it gained a great place in the western basin of the Mediterranean Sea up to the Atlantic Ocean. Algeria was considered the first country to recognize this entity after the Conclusion of the Treaty of Peace and Friendship between the two countries on September 5, 1795. These prisoners wrote their adventures in the form of personal reports and memoirs in which they described their suffering and diaries during the captivity stage. They also described the social life of the Algerians, including customs, traditions, economic activities, and even entertain men, like the politicians, from consuls to doctors, who described Algerian women, even if they were far from their sight and hidden in their hijab and niqab. Another neutral describes what he has seen and heard, linking it to the rules of the Islamic religion and the prevailing social custom in the state. Although American literature on Algeria and Algerian women in particular is very scarce in this period of time, it has given us features of American thought and outlook on the historical scene, despite the newness of the presence of this country in the historical political arena.